121k views
4 votes
How do you simply -12x=12x into an x='s answer?

User BJ Clark
by
6.0k points

1 Answer

4 votes

-12x = 12x

Start by moving all the terms with the variable you want to solve for on one side of the equation and the rest on the other side of the equation.

We will move 12x to the left side of the equation by subtracting 12x from both sides. Now your equation should look like:

-24x = 0

Isolate the variable x by dividing both sides by -24. Everything divided by 0 is equal to 0, so that means x will be equal to 0.

x = 0

Your answer is x = 0.

User Jeroen Mostert
by
5.6k points